Oral adenosine 5'-triphosphate supplementation improved hemodynamic and autonomic parameters after exercise in hypertensive women - de Freitas, Marcelo Conrado [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Freire, Renan Valero [UNESP]; Caperuto, Erico Chagas; Vanderlei, Luiz Carlos Marques [UNESP]; Lira, Fábio Santos [UNESP]; Rossi, Fabrício Eduardo (Korean Society of Exercise Rehabilitation, 2018)
The aim of this study was to verify the autonomic modulation and blood pressure after adenosine-5'-triphosphate (ATP) supplementation asso-ciated to acute aerobic exercise in hypertensive women. Eleven hyper-tensive women (age, 61.8±5.0 years) completed a randomized, double blind trial: ATP supplement condition (ATP=400 mg) or placebo. After 30 min of supplementation or placebo intake, the subjects performed 30 min of aerobic exercise (70%-75% of maximum heart rate). The auto-nomic modulation was assessed by heart rate variability during rest and recovery (postexercise until 30 min of recovery), the square root of the mean squared difference between adjacent RR intervals (RMSSD), standard deviation of successive values (SDNN), low frequency (LF) and high frequency (HF) were measured. The blood pressure (systolic blood pressure [SBP] and diastolic blood pressure, mmHg) were re-corded at rest, immediately postexercise, post-10, post-20, and post-30 min after exercise. For RMSSD, there was statistically significant differ-ence during recovery, with higher RMSSD for ATP compared to placebo (rest=16.4±8.5 vs. placebo=11.6±4.0; ATP=18.5±9.7 msec; P=0.020). When analyzing the delta (recovery minus rest), the RMSSD (ATP=2.1± 7.2 msec vs. placebo=-4.7±7.5 msec; P=0.009), LF (ATP=-19.8±122.7 vs. placebo=-94.1±200.2 msec2; P=0.02), and SDNN (ATP=-2.8±12.2 msec vs. placebo=-10.6±10.5 msec; P=0.010) were higher for ATP than placebo. Furthermore, there was a greater postexercise hypotension at 20 min for ATP (SBP: ATP=-13.2±8.4 mmHg vs. placebo=-6.1±9.9 mmHg; P=0.006). Acute ATP supplementation promoted greater postexercise hypotension for systolic blood pressure and induced faster recovery of heart rate variability in hypertensive women.
Keywords: Aerobic exercise; ATP supplementation; Autonom-ic nervous system; Hypertension; Nutrition